2016
DOI: 10.1016/j.cell.2016.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell Specificity Directs Tolerance versus Allergy against Aeroantigens in Humans

Abstract: FOXP3+ regulatory T cells (Tregs) maintain tolerance against self-antigens and innocuous environmental antigens. However, it is still unknown whether Treg-mediated tolerance is antigen specific and how Treg specificity contributes to the selective loss of tolerance, as observed in human immunopathologies such as allergies. Here, we used antigen-reactive T cell enrichment to identify antigen-specific human Tregs. We demonstrate dominant Treg-mediated tolerance against particulate aeroallergens, such as pollen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
340
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(381 citation statements)
references
References 62 publications
25
340
6
Order By: Relevance
“…171,[200][201][202][203][204] Allergy is finely regulated by CD4 þ CD25 þ Foxp3 þ T-reg cells, [205][206][207] but recent evidence found that this role is particularly related to the immune tolerance mechanism. 208 The role of vitamin D in immune tolerance has recently been addressed 37,119,208,209 and represents a novelty in vitamin D research. Vitamin D participates in CD4þ T-cell differentiation in the thymus, as it should be a fundamental factor able to regulate the level of thymosin-β4 in thymocytes.…”
Section: Role In Acquired and Regulatory Immunitymentioning
confidence: 99%
“…171,[200][201][202][203][204] Allergy is finely regulated by CD4 þ CD25 þ Foxp3 þ T-reg cells, [205][206][207] but recent evidence found that this role is particularly related to the immune tolerance mechanism. 208 The role of vitamin D in immune tolerance has recently been addressed 37,119,208,209 and represents a novelty in vitamin D research. Vitamin D participates in CD4þ T-cell differentiation in the thymus, as it should be a fundamental factor able to regulate the level of thymosin-β4 in thymocytes.…”
Section: Role In Acquired and Regulatory Immunitymentioning
confidence: 99%
“…(Levine et al, 2014), (Vahl et al, 2014). We predict that in health, antigen (epitope)-specificity of Tregs and conventional memory CD4 + T cells would be non-overlapping and mutually exclusive (Golding et al, 2017), (Bacher et al, 2016).…”
Section: Self-nonself Discriminationmentioning
confidence: 98%
“…In the presence of allergen or whole allergen extract, allergen peptide-specific T cells will have expanded and are now present in high abundance, making them easily detectable after restimulation with single peptides. T cell reactivity I response to a peptide can be measured by a variety of assays, most commonly using proliferation, cytokine production, or upregulation of activation marker as a readout [22,36,37]. This method is extremely useful to expand very rare antigen-specific CD4+ populations.…”
Section: Allergen-specific T Cell Frequenciesmentioning
confidence: 99%
“…It acts as a co-stimulatory molecule, binding to CD40 on antigen-presenting cells, which can lead to several downstream events depending on the target cell type. Several studies designed to study allergen-specific effector cells in cohorts suffering from allergy, asthma, or who have been treated with AIT have successfully applied this methodology to immunologically characterize and isolate allergen-specific T cells ex vivo [37,45]. The caveat of using CD154 as a selection marker for activated, allergen-specific T cells is that it is also typically stained intracellularly.…”
Section: Cell Activation Assaysmentioning
confidence: 99%